Thermo and drought tolerance markers and regulation of heat stress proteins for chickpea (Cicer arietinum L.; Fabaceae) production in NE South Africa - Makonya, Givemore Munashe (Department of Biological Sciences, 2020)
Chickpea (Cicer arietinum) is an important legume crop globally ranked third after dry bean (Phaseolus vulgaris) and field pea (Pisum sativum). It constitutes 20% of the total global pulse production and around 95% of its production and consumption takes place in developing countries. Major constraints to chickpea production in sub Saharan Africa (SSA) have broadly been related to abiotic stresses, particularly drought and heat stresses, predicted to increase due to the global climatic changes.Dueto the imperativeness of research for identifying heat tolerance markers for potential chickpea genotype selection, in chapter two of the thesis, the response of four chickpea genotypes to a natural temperature gradient in the field was assessed using chlorophyll fluorescence, non-structural carbohydrate, gas exchange and grain yield. Field experiments were carried out in two winter seasons at three locations with known differences in temperature in NE South Africa. Results showed two genotypes (Acc#3 and Acc#7) were tolerant to heat stress with an Fᵥ/Fₘ of 0.83-0.85 at the warmer site, while the two sensitive genotypes (Acc#RR-2 and Acc#8) showed lower Fᵥ/Fₘ of 0.78-0.80. Both chlorophyll fluorescence measurements: dark-adapted Fᵥ/Fₘ and Fq'/Fₘ' (where Fq' =Fₘ'–F) measured at comparable high light levels correlated positively with grain yield. The two tolerant genotypes also showed higher photosynthetic rates,starch, sucrose and grain yield than the sensitive genotypes at the warmer site. However, these parameters were consistently higher at the cooler than at the warmer sites. It was concluded that genotypes Acc#RR-3 and Acc#7 are heat tolerant and chlorophyll fluorescence and leaf carbohydrates are suitable tools for selection of heat tolerant chickpea genotypes under field conditions. The coolest site of Polokwane showed favourable conditions for chickpea production.Heat and drought stresses are two abioticfactors that often occur simultaneously and are predicted to increase, consequently hampering plant growth. Response of different species to either stresses is well documented but information on the response of the same genotypes to both stresses in chickpea is limited. We aimed to determine whether previously noted heat stress tolerant genotype (Acc#7) is drought tolerant and the heat sensitive (Acc#8) is drought sensitive, and whether intermittent moisture supply at vegetative stage would induce priming effect to later drought at flowering. At vegetative stage, plants were divided into three groups, non-stressed (watered to 75% field capacity (FC), severe water stress (moisture-withholding for 14 days) and treated to 40% FC throughout the experiment (mild-stress), with recovery for the severely stressed plants after which they were stressed (double-stress) at flowering. Drought treatments at vegetative and flowering growth stages decreased physiological parameters and biomass accumulation in both genotypesexcept low water supply at 40% FC that decreased biomass in Acc#7 but not Acc#8. Double drought stress resulted in priming effect in Acc#7, having higher biomass, chlorophyll fluorescence, stomatal conductance, net photosynthesis, and relative water content in comparison to the introduction of stress only at flowering growth stage, as well as in comparison to Acc#8. These results showed that both Acc#7 and Acc#8 are sensitive to drought whereas after priming Acc#7 is better acclimated to drought than Acc#8 associated with osmotic adjustment on leaf relative water content (RWC) and higher capacity to protect photosynthetic activity, making Acc#7 potentially ideal for areas associated with intermittent drought spells. This observation, however, disapproved the hypothesis that Acc#7 is more drought tolerant than Acc#8 but is rather better acclimated than Acc#8, because of its superiority only in primed plants and not those stressed only at either vegetative or flowering stages. The findings emphasise the importance of matching chickpea physiological performance to expected rainfall amounts and distribution in drought prone areas during genotype selection. Chapter four of the thesis was an interrogative proteome analysis of the differences in the heat tolerant and sensitive chickpea (Cicer arietinumL.; Fabaceae) genotypes along a temperature gradient under field conditions which will help in identifying the molecular mechanisms involved in the crop's tolerance. Few studies have thus far combined chickpea physiological and proteome analysis to elucidate the changes in abundance and/or activity of relevant enzymes and expression of heat responsive proteins. In this study, analyses of chlorophyll concentrations, gas exchange, flavonoids and anthocyanin concentrations from a chamber experiment, as well as proteomic parameters from field studies in both the heat tolerant and sensitive genotypes are presented. The heat tolerant genotype Acc#7 maintained unaltered physiological performance at flowering growth stage when exposed to high (35/30°C) and moderate (30/25°C) heat stress, under climate chamber conditions compared to the two heat susceptible genotypes (Acc#RR-2 and Acc#8). Results from the proteomic studies showed an up-regulation in proteins related to protein synthesis (e.g. ribulose bisphosphate carboxylase/oxygenase activase), intracellular traffic (e.g. mitochondrial dicarboxylate/tricarboxylate transporter DTC), defence (e.g. HSP70) and transport (e.g. GTP-binding protein SAR1A-like) in heat tolerant Acc#7 compared to the susceptible Acc#8. Results from KEGG analyses support the involvement of probable sucrose-phosphate synthase and sucrose-phosphate phosphatase proteins in the starch and sucrose pathway,that were up-regulated in the heat tolerant genotype Acc#7. This result was in support of our earlier report where tolerant genotype Acc#7 had higher leaf starch and sucrose concentrations in comparison to the susceptible genotype Acc#8. The presence of these differentially regulated proteins including HSP70, ribulose bisphosphate carboxylase/oxygenase activase, plastocyanin and protoporphyrinogen oxidase shows their potential role in field grown chickpea tolerance to heat stress at flowering growth stage. In conclusion, chlorophyll fluorescence (both Fᵥ/Fₘ and Fq'/Fₘ') and leaf carbohydrates were identified as selection markers that can potentially be used for chickpea phenotyping for heat stress under field conditions with the chlorophyll fluorescence parameters correlating positively with seed yield. Due to its higher biomass, chlorophyll fluorescence (Fᵥ/Fₘ), stomatal conductance, net photosynthesis and RWC, heat tolerant genotype Acc#7 was identified to have better adaptive tolerance to drought stress after priming through exposure to intermittent dry spells than Acc#8. Furthermore, under controlled climate chamber conditions, Acc#7 consistently showed characteristics of tolerance to heat stress while Acc#RR-2 and Acc#8 were heat susceptible. Higher chlorophyll fluorescence, grain yield, chlorophyll concentrations, gas exchange, flavonoids and anthocyanin concentrations for Acc#7 compared to Acc#8 in the climate chamber was further validated by the higher up-regulation of proteins involved in protein synthesis, intracellular traffic, defence and transport in Acc#7 compared to Acc#8. The incorporation of proteomics in heat and drought stress studies will potentially help further the understanding of mechanisms by which the crop responds to these stresses.